Plagiarism and Predatory Publishing - Padua, Roberto N. (JPAIR Multidisciplinary Research, 2013)
The paper tackles the issue of predatory journals and publishers. Jeffrey Beall (2012), librarian at the University of Colorado, coined the term ‘predatory publishers’ and defines them as “... those that unprofessionally exploit the author-pays model of open-access publishing (Gold OA) for their own profit.” A socio-economic model for predatory publishing similar to the law of supply and demand in economics is proposed and made as basis for analyzing what can be done to eliminate this unethical practice. The paper concludes that, based on the model, the only way to stop the practice is to strengthen the nation’s higher education quality assurance system in research; institute national research journal accreditation systems and emphasize the value of professionalism and intellectual honesty in the academe.
Keywords: predatory publishing; plagiarism; journal accreditation service